Environmental Impact Analysis for Communities in Oil Palm Plantations - Willya Achmad (Journal of Economics and Business (JECOMBI), 2024)
The existence of the industrial sector and oil palm plantations can be a driving force for the local community's economy, but the existence of the industrial sector and oil palm plantations does not always have a positive impact, but has a negative impact on the surrounding community, especially the workers who work on the plantation. This study aims to determine the environmental impact for workers working in oil palm industry and plantations. This study uses a qualitative approach with a descriptive method. The results show that the history of the opening of oil palm plantations is in order to create jobs, improve the living standards of the surrounding community and of course improve the country's economy through foreign exchange earnings. However, the existence of oil palm industry and plantations does not always have a positive impact but also has a negative impact, especially environmental health for the community and workers where there is a decrease in the quality and quantity of clean water, pesticide poisoning, the emergence of diseases caused by the industry and oil palm plantations.